2013
DOI: 10.17221/8/2013-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

The Italian olive oil industry in the global competitive scenario

Abstract: Th e current paper analyzes the reasons behind the diffi culties of the Italian olive oil industry to compete in the world markets. Th e analysis highlights that these complexities can be related with two core factors: stagnant demand in the main producer/consumer countries and strong competition arising from the Spanish olive oil industry increasingly involved also in processing and trade. In addition, these weakness factors are boosted by the market power exerted by large retail chains that are now the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
(32 reference statements)
0
10
0
2
Order By: Relevance
“…Stella Cilento 14%; San Mauro Cilento 11%). The reasons for poverty lock-ins in the four communities are complex and closely associated with structural and socio-economic constraints that characterise economic development in southern Italy (Pomarici and Vecchio, 2013), but factors such as land fragmentation, small farms (average only 2.4 ha) and few opportunities for work are among the most important constraints. As Figure 2 shows, poverty emerges as a key lock-in contributing to 'very low' resilience.…”
Section: Economic and Structural Lock-insmentioning
confidence: 99%
See 1 more Smart Citation
“…Stella Cilento 14%; San Mauro Cilento 11%). The reasons for poverty lock-ins in the four communities are complex and closely associated with structural and socio-economic constraints that characterise economic development in southern Italy (Pomarici and Vecchio, 2013), but factors such as land fragmentation, small farms (average only 2.4 ha) and few opportunities for work are among the most important constraints. As Figure 2 shows, poverty emerges as a key lock-in contributing to 'very low' resilience.…”
Section: Economic and Structural Lock-insmentioning
confidence: 99%
“…Interviews suggested that smaller farmers often lacked confidence, experience and/or capacity to tackle complex forms and cope with the application process, especially when it came to subsidies for farm diversification or on-farm processing. Respondents also felt that there was a lack of information about what subsidies are available, and lack of support for individuals in accessing available funding (see also Pomarici and Vecchio, 2013). However, while most interviewed farmers agreed that agricultural subsidies played a relatively important part in farm survival for some, access to funds from external sources was not available as eligibility is largely based on asset availability and specific socio-economic characteristics of each farm.…”
Section: Economic and Structural Lock-insmentioning
confidence: 99%
“…Son dönemde zeytinyağının sağlık açısından faydası üzerine farkındalığın artmasıyla birlikte (Harwood ve Yaqoop, 2002;Mili, 2001), zeytin ürününün dünyadaki önemi de gün geçtikçe artmaktadır. Uluslararası yayınlarda bu ürün ile ilgili özellikle zeytinyağı konusunda ayrıntılı analizler içeren (Mili, 2001;Mili ve Zúñiga, 2001;Mili, 2002;Carri ve Sassi, 2003;Karipidis vd., 2005;Kailis ve Harris, 2007;Scheidel ve Krausmann, 2011;Pomarici, 2013) çeşitli çalışmalara rastlansa da Türkiye'de zeytinin ticari bağlamda analiz edildiği literatürün sınırlı olduğu görülmektedir (Duran, 2006;AYSO, 2012;Gümrük ve Ticaret Bakanlığı, 2016;Metin ve Atlı, 2016). Türkçe literatürde zeytin ticareti konusunda daha çok, çeşitli kurumlar tarafından yayınlanan raporlar ve tarımsal bir ürün olmasının da bir nedeni olarak tarım ekonomisi alanında yapılan çalışmalar bulunmaktadır.…”
Section: Literatürunclassified
“…Bu açıdan özellikle Yunan ekonomisinde zeytin ürünü özel bir öneme sahiptir (Karipidis vd, 2005). AB politikaları gereği sağlanan destekler sayesinde İspanya, İtalya ve Yunanistan'ın sofralık zeytin ve zeytinyağı ihracatında dünya lideri olduğu görülmektedir (Pomarici, 2013;Scheidel ve Krausmann, 2011). AB'nin geliştirdiği politikalar sonucunda, Türkiye'ye kıyasla dünya ticaretinde daha güvenilir ve etkin konumda olduğunu söylemek mümkündür (Toplu Yılmaz, 2013: 37).…”
Section: Literatürunclassified
“…In those countries, olive growing has an outstanding economic and social importance (MAPAMA, 2016), playing an important role as economic activity in a large number of rural areas. Currently, the decrease of competitiveness in olive sector threatens the survival of olive farms and mills (Pomarici & Vecchio, 2013), that needs to improve farm efficiency through modernisation, shared machinery management or outsourcing labours (Vilar-Hernández et al, 2011). In the last decades, olive orchards management evolved towards more intense planting densities and use of high level of mechanization (Novello et al, 2014); however, there is still margin for improvement in the farming techniques (CarmonaTorres et al, 2014).…”
Section: Introductionmentioning
confidence: 99%